Analisis Perbandingan Hasil Belajar Bahasa Indonesia Melalui Luring SMP Negeri 5 Makassar dan Daring SMP Kartika Wirabuana Makassar - Isnani Arianti (Peneliti.net, 2022)
Comparative analysis of Indonesian language learning outcomes through offline SMP Negeri 5 Makassar and online SMP Kartika Wirabuana Makassar. This research is a descriptive type of research that uses a